Dynamic selective information hiding based on search order coding with low bit rate. (September 2015) - Chang, C.-C.; Lin, M.-C.; Cheng, T.-F.
<x content-type="archive" xml:space="preserve">Abstract</x> A low bit rate information hiding scheme is important for efficient communication. According to our observation, in a search order coding based (SOC based) hiding method, the case distribution generated from different images and from different secret strings is different. Based on this characteristic, we designed a dynamic selective, SOC based, information hiding scheme to achieve a desirable compression effect. That is, depending on different case distributions, we used different coding modes to reduce the bit rate more effectively. The main concept of our design is to let the two cases that occur most frequently use one-bit indicators and to let the remaining two cases use four-bit indicators to indicate the following coding types. The experimental results showed that the proposed scheme has a lower bit rate than other SOC based information hiding schemes. As a result, the proposed information hiding scheme is more practical for real world applications.